FAKTOR YANG MEMPENGARUHI USE BEHAVIOR PADA PENGGUNAAN PLATFORM E-COMMERCE DALAM PEMESANAN KAMAR MENGGUNAKAN MODEL UTAUT DI THE ZHM PREMIERE HOTEL PADANG - Reza Amelia; Feri Ferdian (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Based on data on the e-commerce platform in booking rooms at The ZHM Premiere Hotel Padang, guest instability was found in booking rooms through the e-commerce platform from August 2022 - January 2023. This study aims to analyze factors that influence usage behavior on the use of the e-platform -commerce in booking rooms using the UTAUT model at The ZHM Premiere Hotel Padang. The independent variables examined in this study were Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Conditions and Habits on Use Behavior using the PLS-SEM analysis technique. The results of this study indicate that the variables Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Conditions have a positive effect on use behavior.Keywords: Usage Behavior, E-Commerce Platform, PLS-SEM, UTAUT